Heat transmission across fouled tubes analysed by Trefftz approach - Skiepko, Teodor (Computer Assisted Methods in Engineering and Science, 2023)
The paper presents application of the Trefftz method for analysis a case of heat conduction problem across two coupled regions - fouling layer of complex form deposited onto the tube wall at its outer periphery. Taken into considerations modes of heat transfer from a hot gas to the outer surface of the fouling layer are: either by pure convection or radiation, and by both the modes combined. A fluid flowing inside the tube exchanges heat by only convection at constant transfer coeffcient. Based on the variational principle and Trefftz method the boundary weighted residual approach has been developed providing in turn an equation system for analysis of the problem under study. Then, results of series of systematic numerical experiments illustrating convergence and accuracy of the approach when applied to the case in point have been shown for a specific input data set assumed. To emphasise practical significance of the method, a calculated temperature distribution 3D chart and thermal resistance of 2D fouling deposits conclude the paper.